Commoning of territorial heritage and tools of participated sustainability for the production and enhancement of agro-environmental public goods - G. Fabiola Safonte; Claudio Bellia; Pietro Columba (Agricultural and Food Economics, 2021)
The purpose of this paper is to analyze how the commoning heritage processes find application for the production of agro-environmental public goods in contexts of high socio-economic marginality and environmental vulnerability, characterized by abandonment and from the consumption of agricultural land for food use. The purpose is to understand how these processes are able to influence, at local level, the governance processes for the implementation of environmental protection strategies. The survey made it possible to verify how the commoning processes aimed at the production of agro-environmental goods generate territorial resilience, understood as a community competence able to structure specific forms of social learning based on priorities identified and defined by the communities. The followed theoretical framework and the methodological approach have allowed on the one hand to draw up a taxonomy of the different territorial dynamics and on the other to identify a mixed indicator system, applicable and replicable also in other contexts, able to describe its dimensions analytically. The assessment of the cognitive elements related to the territorial fabric carried out through the proposed approach has allowed to demonstrate how the knowledge of the territorial capital contributes to the activation of forms of collective intelligence necessary for decision-making processes.
Keywords: 330; Agro-environmental public goods; Collective actions; Inner areas; Marginality; Rural areas; Territorial capital; Vulnerability